Pemanfaatan Aquaponic di Wilayah Kavling Rawa Bunga, Tangerang Selatan - Karyadi; Rizki Aulia Nanda; Amir; Fathan Mubina Dewadi (Faculty of Economics and Business YARSI University, Jakarta, Indonesia, 2022)
This community service is a form of service or contribution to the community by collaborating on research and teaching that has been carried out in universities. The purpose of this activity is to provide an understanding for the community of the importance of innovating so that later it can be used as a place for entrepreneurship. The phenomena of the problems faced in this activity are human resources in the swamp flower plots that are not yet qualified for technological innovation activities. The method used is by observing activities that are often encountered, namely hydroponic. However, other innovations from hydroponics are needed, namely aquaponics with a slightly different method. With this difference, the related parties can get out of their comfort zone so that they can find a solution to the joint planting of kale. If further collaborated, then with the long term it can be relied on upon entrepreneurship.